Determination of Film Recommendations using the Generalized Sequence Pattern (GSP) Association Method - Acep Razif Andriyan; Dinda Meysya Rochma; Melani Nur Mudyawati; Miftahul Jannah; Siti Lufia Dwi Agustini; Arham Aulia Nugraha (UIN Sunan Gunung Djati Bandung, 2021)
Along with the development of the times, films are used as a medium of communication and as a medium of entertainment that can be watched by fans everywhere. The high level of film enthusiasts makes viewing patterns that can be used as recommendation data. Besides, this system can provide benefits to the company concerned. This study used the Generalized Sequential Pattern (GSP) Algorithm with the Association Mining method. The primary function is to find the sequence or sequential of a set of attributes that often appear together to see the results to find out the recommendation data information after the previous film runs out.